(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Hysterosalpingography (HSG) has been used for nearly 100 years as a common method applied in routine use toinvestigate the causes of female infertility. It is used to evaluate the uterus and both tubes of the uterus by using X-raysin the presence of contrast agent. The development process of this method, which is called uterine film among the people,has spread over a wide period of time. In 1902, researcher Kelling suggested the investigation of the tubes by deliveringgas during laparoscopy. It is known that Nemchow wanted to visualize the inside of the uterus with the help of Lugol'ssolution in 1909. Researcher Rindfleish used aqueous bismuth paste to apply this method in 1910. Lovey succeeded inobserving the tubes in 1912 by injecting isotonic colloidal silver solution into the uterine cavity.